Judicial Efficiency and Banks Credit Risk Exposure - Giulia Canzian; Antonella Rita Ferrara (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We exploit the outset of a regulation seeking to improve judicial efficiency through the rearrangement of courts' geography in Italy to provide causal evidence on the relationship between judiciary structural reforms and banks financial stability. To this end, we apply a difference-in-differences approach on a dataset on annual proceedings handled by each court over the period 2010-2017, complemented by banks balance sheet information. Our findings yield a negative effect of the reform on both judicial efficiency and Non-Performing Loans ratio. Furthermore, we identify heterogeneous effects based on the existing capacity of the courts to dispose of pending proceedings and geographical location. Digging deeper into this mechanism, we set up a causal mediation analysis to prove that the judicial system affects banks credit risk exposure both indirectly (through judicial efficiency) and directly, thereby influencing borrowers who react to the perceived enforcement.
Keywords: D04; G21; P43; 330; judicial efficiency; non-performing loans; justice reform; difference-in-differences; mediation analysis